RIGHT VENTRICULAR MYOCARDIAL INFARCTION IN A PATIENT WITH CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION AGAINST THE BACKGROUND OF SMALL CORONARY ARTERIES - O. A. Arkhipova; E. G. Kuznetsova; T. V. Martynyuk; I. Ye. Chazova (Евразийский Кардиологический Журнал)
Most often acute myocardial infarction of the right ventricle is diagnosed in patients with acute left ventricular lesion and is associated with an atherosclerotic process in the coronary arteries. Isolated acute myocardial infarction of the right ventricle is rarely diagnosed and is often detected only during autopsy. Previously it was believed that in the absence of a significant lesion of the coronary arteries, an acute myocardial infarction of the right ventricle is associated with hypertrophy of the right ventricular myocardium. The results of a study in which acute myocardial infarction of the right ventricle were found in patients who died due to acute massive pulmonary embolism and who did not have right ventricular hypertrophy appeared later. There are many questions regarding the tactics of therapy for this complication, especially in patients with pulmonary hypertension who are on treatment with pulmonary arterial vasodilators. The article describes a rare clinical case of postmortem detection of myocardial infarction of the right ventricle against the background of small coronary arteries in a 41-year-old patient with a diagnosis of chronic thromboembolic pulmonary hypertension, the difficulties of intravital diagnosis and the restriction of drug therapy.